Radiofrequency catheter ablation of atrioventricular nodal reentry tachycardia in children and adolescents: a single center experience - Myung Chul Hyun (Korean Journal of Pediatrics, 2017)
PurposeAtrioventricular nodal reentry tachycardia (AVNRT) is less common in pediatric patients than in adult patients. Thus, data for pediatric AVNRT patients are insufficient. Hence, we aimed to analyze the patient characteristics, treatment, and any recurrences in pediatric AVNRT patients.MethodsWe reviewed the records of 50 pediatric AVNRT patients who had undergone radiofrequency catheter ablation (RFCA) between January 1998 and December 2016 at a single regional center. The patients were aged ≤18 years.ResultsAmong 190 pediatric patients who underwent RFCA for tachyarrhythmia, 50 (26.3%; mean age, 13.4±2.6 years) were diagnosed as having AVNRT by electrophysiological study. Twenty-five patients (25 of 50, 50%) were male. Twenty patients (20 of 50, 40%) used beta-blockers before RFCA. All patients had no structural heart disease except 1 patient with valvular aortic stenosis and coarctation of the aorta. RFCA was performed using the anatomic approach under fluoroscopic guidance. The most common successfully ablated region was the midseptal region (25 of 50, 50%). Slow pathway (SP) ablation and SP modulation were performed in 43 and 6 patients, respectively. Complication occurred in 1 patient with complete atrioventricular block. During follow-up, 6 patients had recurrence of supraventricular tachycardia, as confirmed by electrocardiography. Among them, 5 underwent successful ablation at the first procedure. In 1 patient, induction failed during the first procedure.ConclusionRFCA is safe and effective in pediatric AVNRT patients. However, further research is needed for establishing the endpoints of ablation in pediatric AVNRT patients and for identifying risk factors by evaluating data on AVNRT recurrence after RFCA.